Persepsi Pengunjung terhadap Penyelenggaraan Geobeat Ecotopia sebagai Implementasi Sustainable Event di Geo Open Space, Kerobokan Kelod - Kurnia Cahyani, Stefani Rosa; Ratri Paramita; Ketut Arjaya (Journal of Event and Convention Management, 2023)
The surge in both domestic and international tourists has contributed to the growth of events in Bali; however, many of these events have yet to adopt sustainable practices. This study aims to explore visitor perceptions of GeoBeat Ecotopia as a model of a sustainable event, which can serve as a reference for future sustainable event implementation. A descriptive quantitative method was employed using Silvers’ six-dimension theory and a Likert scale, targeting 80 respondents out of a total population of 409 visitors through probability sampling with a simple random sampling approach. Data were collected through observation, questionnaires, interviews, and documentation studies. The overall results indicate a very positive perception (average score of 4.66), with individual dimension scores as follows: activity (4.76), atmosphere (4.75), arrival (4.71), anticipation (4.59), amenities (4.65), and appetite (4.51). The highest-rated dimension was activity, while the lowest was appetite.